2016
DOI: 10.1128/jvi.01706-15
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Host-Polerovirus Interaction Topologies Using Protein Interaction Reporter Technology

Abstract: Demonstrating direct interactions between host and virus proteins during infection is a major goal and challenge for the field of virology. Most protein interactions are not binary or easily amenable to structural determination. Using infectious preparations of a polerovirus (Potato leafroll virus [PLRV]) and protein interaction reporter (PIR), a revolutionary technology that couples a mass spectrometric-cleavable chemical cross-linker with high-resolution mass spectrometry, we provide the first report of a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 85 publications
(147 reference statements)
0
77
0
Order By: Relevance
“…bacterial lacZ gene and the yeast HIS3 gene, which are both controlled by the LexA operators [29,30]. Another novel reporter system that has been created for Y2H assays utilizes an enhanced green fluorescent protein (EGFP)-based reporter in order to characterize interactions.…”
Section: Y2h Pairwise Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…bacterial lacZ gene and the yeast HIS3 gene, which are both controlled by the LexA operators [29,30]. Another novel reporter system that has been created for Y2H assays utilizes an enhanced green fluorescent protein (EGFP)-based reporter in order to characterize interactions.…”
Section: Y2h Pairwise Screeningmentioning
confidence: 99%
“…1). Modifying protein structures through mutation or domain deletion can reveal functionally significant PPIs and increase understanding of the structure function relationships of your POIs [29,30]. Mechanism-based trapping of interactors by protein engineering can increase binding affinity and has been applied to kinases, phosphatases, proteases, E3 ligases, and many other protein types [29,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Although this technology has not yet been applied in human infections, the study found several instances of interaction topologies that could reflect conserved functions in unrelated human viruses. For example, a PLRV-host interaction was identified that was analogous to the known structural bind-ing of the animal zinc binding protein BS69 to a conserved PXLXP motif in viral proteins from the Heresviridae and Adenoviridae families (84). Overall, this technology has enormous potential in pathogen proteomics, with the ability to identify in a single experiment both the interacting protein pairs and the higher order structures that mediate the interaction.…”
Section: Host Cell Proteomes Under Infection-pathogen Infectionmentioning
confidence: 99%
“…Toward this goal, the continued development of in vivo chemical labeling techniques paired with mass spectrometry will increase the specificity of identifying interactions in infected cells and provide the direct points of hostpathogen contact. For instance, an in vivo chemical crosslinking strategy paired with protein interaction reporter technology and mass spectrometry analysis has been used to identify protein interaction interfaces in cultured cells (83), viruses (84), and bacteria (85). The first application of this technology to viral infection characterized the protein interaction topologies of the plant pathogen Potato leafroll virus (PLRV) (84).…”
Section: Host Cell Proteomes Under Infection-pathogen Infectionmentioning
confidence: 99%
See 1 more Smart Citation